The Legal Status of Conscription in Ukraine: Between National Jurisdiction and International Law - Anatoliy Yatsyshyn; Maksym Filipov; Ivan Bashta; Maryna Kleiman; Serhii Baranov (Tirtayasa Journal of International Law, 2026)
This study examines the administrative and legal framework that regulates the activities of entities responsible for conscription and mobilization in Ukraine under conditions of martial law. The analysis focuses on the legal status, powers, and institutional authority of state bodies, local government bodies, territorial recruitment and social support centers, as well as civil society actors involved in mobilization processes. The scope of the legal analysis covers both national legal documents regulating mobilization and specific international and comparative approaches to organizing conscription systems and civil-military coordination during periods of armed conflict. Using formal-legal, comparative-legal, and systematic methods, the study identifies the main categories of conscription support entities, including bodies with general, special, and specialized jurisdiction. The comparative dimension of the study is limited to an examination of international scholarly approaches and foreign legal models regarding the management of mobilization, civil-military interaction, and administrative coordination in wartime. The findings reveal significant shortcomings in the legal regulation of these entities, including unclear delineation of powers, overlapping responsibilities, and the lack of a comprehensive legal framework governing regional recruitment and social support centers. The study argues that improving the institutional clarity and legal regulation of mobilization authorities’ activities is essential for enhancing administrative efficiency, legal certainty, and defence capabilities under conditions of prolonged martial law.